Modelo ProLab: Coffee Net – Comunidad virtual para fomentar el consumo de café peruano. - Cespedes Reynaga, Vitaly Uriel (2025)
The coffee sector in Peru faces significant challenges, since more than 50% of the coffee consumed domestically is imported, and is predominantly in soluble forms (Cafelab.pe, 2024). The local coffee consumed is mostly of low quality (Agencia Agraria de Noticias, 2024), including discards and mixtures with sugar and other grains, according to studies carried out by the Central Café & Cacao (Cafelab.pe, 2024), which represents 11 cooperatives from regions such as Junín, Ayacucho, Cusco and Puno (Cafelab.pe, 2024). This scenario underlines an imbalance in the market that directly affects the perception and consumption of quality national products. The relevant social problem in the industry focuses on coffee cooperatives, which seek to diversify their economic activities without compromising their export capacity. This situation directly affects rural communities that depend on these cooperatives as their main source of income. To address this issue, “Coffee Net” has been developed, an innovative digital ecosystem designed to connect coffee lovers directly with Peru’s rich coffee heritage. Coffee Net is a digital platform that allows consumers to buy coffee directly from producers, providing an educational and efficient shopping experience that stands out for its commitment to sustainability, quality and economic support to coffee-growing communities. From a financial point of view, “Coffee Net” presents promising indicators. The Present Value (PV) of the project is S/. 3,874,727, which indicates the total value generated. The initial investment required is S/. 175,613.33. The Net Present Value (NPV) is S/. 3,699,113.55, which suggests that the project generates positive net profitability after covering costs and investments. The Internal Rate of Return (IRR) is 467.84%, which indicates high profitability. Finally, the Social NPV calculated for "Coffee Net" amounts to S/. 6,121,468.72, indicating that, from a social and economic perspective, the project is not only viable but also highly beneficial.